Performance appraisal: Dimensions and determinants - Alberto Bayo-Moriones; José Enrique Galdón-Sánchez; Sara Martinez-de-Morentin (Institute for the Study of Labor (IZA), 2011)
The determinants of the dimensions that shape a formal system of performance appraisal are studied in relation to a sample of Spanish manufacturing establishments. In particular, the factors that influence the measures used to evaluate performance, the person who carries out such appraisal and its frequency are analysed. Our results show that the characteristics of the establishment exert a significant influence on the configuration of performance appraisal. Specifically, we find that the use of practices complementary to performance evaluation and the structural factors of the establishment are found to correlate closely with the dimensions of formal performance appraisal.
urn:nbn:de:101:1-201104134267
Keywords: M12; M5; 330; performance appraisal; monitoring; establishment characteristics; dimensions of appraisa; Leistungsbeurteilung; Verarbeitendes Gewerbe; Unternehmen; Spanien